Evidence and Ideology in the Independent Review of Prevent - Stuart Macdonald (Journal for Deradicalization, 2024)
A key part of the United Kingdom’s counter-terrorism framework, the Prevent Strategy is designed to operate ‘upstream’ to stop people becoming or supporting terrorists. In February 2023 the long-awaited independent review of Prevent reported, evaluating the Strategy against its core objectives. Led by Sir William Shawcross, the report claimed that Prevent’s overarching rationale remains good because the UK continues to face a genuine terrorist threat, but lamented its diversion toward safeguarding and its downplaying of Islamist extremism as the purportedly most pressing source of radicalisation within the UK today. To declare the reception to Shawcross’ report mixed would be generous, with some observers even demanding that the Government withdraw the review. We share many concerns raised by civil society groups and practitioners, and in this piece argue that the Review is fundamentally flawed because of its partial – in the sense of both limited and biased – engagement with the relevant (and extensive) knowledge base that exists around radicalisation, counter radicalisation, and Prevent. More specifically – and with particular attention to the report’s emphasis on ‘ideology’ – we show: (i) that the report suffers from a selective, and problematic, engagement with relevant academic research that poorly represents established knowledge in this area; (ii) that this selective engagement leads to a questionable, and highly contestable, conceptual framing of the report’s core terms and parameters; and, (iii) that this contestable framing has implications for operationalisation of the report’s findings. In doing this, the article makes three core contributions in (i) situating the Shawcross review in relevant historical and policy contexts; (ii) offering original analytical critique of the review’s methodological and political assumptions and findings; and, (iii) extending research on the mechanisms of counter-terrorism review via this new – and underexplored – case study.